Studi Kasus: Asuhan Keperawatan pada Orang dengan Gangguan Jiwa dengan Perilaku Kekerasan : Case Study: Nursing Care for Individuals with Mental Disorders and Violent Behavior - Nurul Ainul Shifa; Aisyah Safitri (MPI Press, 2021)
Introduction: Perilaku kekerasan adalah suatu keadaan seseorang melakukan tindakan yang dapat membahayakan secara fisik baik terhadap diri sendiri, orang lain dan lingkungan. Dampak atau perubahan yang terjadi dapat berupa perasaan tidak sabar, cepat marah, dari segi sosial kasar, menarik diri, dan agresif. Objectives: The purpose of this study was to determine the appropriate nursing care and intervention in patients with a diagnosis of violent behavior. Method: The design in this study is a case study design using a nursing process approach. The sample in this study was Mr. J. The sampling technique used was simple random sampling. The research was conducted at X Hospital in April 2021. Data was collected by means of interviews, observations, and documentation studies. The research instrument is using the mental nursing care format and the SOP on Implementation Strategy (SP). The nursing process approach carried out by researchers includes the following stages: Assessment Researchers collect data, both from respondents/patients. Nursing diagnoses, make nursing interventions, carry out implementation and then carry out nursing evaluations. Result: The client was escorted by his family on the grounds of fighting with his friends, feeling humiliated for not working, drugs being hidden and not being taken, being angry at home, speaking rudely and throwing tantrums, having trouble sleeping, the patient dropped out of medicine for approximately 4 weeks Mr. J had previously been admitted to the hospital with the same case, namely violent behavior. There are no families with mental disorders, the patient's communication pattern is closed with the family and the parenting pattern of the client's family is authoritarian. Conclution: The main nursing problem is violent behavior.